2010
DOI: 10.1016/j.intman.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of psychic distance

Abstract: This study investigates the antecedents of psychic distance. Building on original data in 25 of the world's largest economies, we investigate potential drivers of the perceived distance among a given pair of countries. Results confirm that psychic distance is indeed a multifaceted construct which is determined by cultural, geographic and economic factors. Furthermore, our results indicate that geographic distance accounts for the largest share of the explained variance, suggesting that future studies should at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
310
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 353 publications
(333 citation statements)
references
References 56 publications
13
310
1
9
Order By: Relevance
“…Here we put this claim to test -do their recommendations indeed increase the rigor of country-based culture research? Specifically, we replicate a published study : Håkanson & Ambos' (2010) analysis of psychic distance. Psychic distance is referred to as factors preventing or disturbing the flow of information between potential and actual suppliers and customers (Johanson & Vahlne, 1977, p. 24), and is frequently used to explain expansion patterns of internationalizing firms.…”
Section: Putting Klg's Recommendations To Testmentioning
confidence: 95%
See 2 more Smart Citations
“…Here we put this claim to test -do their recommendations indeed increase the rigor of country-based culture research? Specifically, we replicate a published study : Håkanson & Ambos' (2010) analysis of psychic distance. Psychic distance is referred to as factors preventing or disturbing the flow of information between potential and actual suppliers and customers (Johanson & Vahlne, 1977, p. 24), and is frequently used to explain expansion patterns of internationalizing firms.…”
Section: Putting Klg's Recommendations To Testmentioning
confidence: 95%
“…Unlike cultural distance which is based on a comparison of 'objective' sets of values that people in different countries hold, psychic distance is in essence perceptual. Håkanson & Ambos (2010) empirically tested the relationship between cultural distance and psychic distance (average countrylevel perception of distance), while controlling for geographic and economic distance. They found that cultural distance is positively related to psychic distance, but the effect of cultural distance is relatively smaller than that of geographic distance.…”
Section: Putting Klg's Recommendations To Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on expatriates, Selmer et al (2007) concluded that German expatriates assigned to the US were better adjusted than US expatriates assigned to Germany. Håkanson and Ambos (2010) argued that managers from a country with a well-defined regulatory environment and transparent governance structures experience huge difficulties in countries with weak formal institutions. By contrast, managers from countries with weak institutional structures may not experience the same difficulties in countries with more developed and transparent institutions that are easier to understand.…”
Section: Symmetric and Asymmetric Proximities In Mandamentioning
confidence: 99%
“…By contrast, managers from countries with weak institutional structures may not experience the same difficulties in countries with more developed and transparent institutions that are easier to understand. Another example of asymmetry in the study by Håkanson and Ambos (2010) concerns the size of countries and their political and cultural influence. For instance, despite sharing the same language, Belgian newspapers and other media are more likely to report on developments in France than the other way around, which creates asymmetry in the perceived distance between the two countries.…”
Section: Symmetric and Asymmetric Proximities In Mandamentioning
confidence: 99%